Faktor Risiko Usia, Pekerjaan Dan Paparan Asap RokokPada Ibu Dengan Kejadian Berat Bayi Lahir Rendah DiKecamatan Banyudono Kabupaten Boyolali - Narita, Agnes; , Yuli Kusumawati, SKM., M.Kes; , Anisa Catur Wijayanti, SKM., M.Epid (2016)
Infant mortality rate in Indonesia was still an issue that has yet to be solvet properly, and low birth weight was a risk factor that is the most frequentcause of infant mortality rate. However, many factors also affected low birth rate, such as maternal factor mother, infant, and the environmental factor. The purpose of this study was to understand the relation between risk factors as age, occupation and exposure to cigarette smoke in the mother with low birth weight incidence at Banyudono, Boyolali. This research was analytic observasional with case control design. Sample consent of 45 sample case (LBW) and 45 sample control (NBW). Dependent variable in this research was LBW, independent variable are age, occupation, secondhand smoke exposure in the mother and confounding variable are nutrition status, anemia, ANC visit frequency. Statistic analysis use chi square test and stratification analysis with mantel handzel test. The results showed that there was relationship between age (p velue: 0,016; OR:3,9; 95%CI: 1,38-11,27), secondhand smoke exposure in the mother (p velue p: 0,003; OR:4,01; 95%CI: 1,66-9,65) and there was no relationship between occupation (p velue: 0,62) with low birth weight infants incidence at Banyudono, Boyolali. The relationship risk factors as age and secondhand smoke exposure in the mother with low birth weight infants incidence was not confounded with nutrition status, anemia, ANC visit frequency.